Effect of microbial immunostimulants on WSSV infection percentage and the expression of immune-related genes in white shrimp (Litopenaeus vannamei) - Fierro Coronado, Jesús A.; Luna González, Antonio; Caceres Martínez, Carlos J.; Álvarez Ruiz, Píndaro; Escamilla-Montes, Ruth; González Ocampo, Héctor A.; Peraza-Gómez, Viridiana (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: The white spot syndrome virus (WSSV) causes high mortalities in aquaculture. The use of immunostimulants increases animal resistance. Objective: To evaluate the WSSV infection percentage and the immunostimulant effect of lactic acid bacteria and yeast (MI= microbial immunostimulants) on WSSV infected Litopenaeus vannamei. Methods: A bioassay was performed for 33 d, with treatments in triplicate. The MI was added to the feed at 8.5 mg/kg feed and offered to shrimp (9.9 ± 3.1 g) daily, every 2 days, or every 3 days. Shrimp were infected with WSSV at 9 and 19 days. The expression of four immune system-related genes was studied using qRT-PCR. Results: No significant differences were observed in growth and survival among treatments. At the end of the bioassay, WSSV infection percentage (low viral load) decreased 8.3 and 25% in treatments III and IV as compared to the control group. Treatments with MI showed significant differences in the relative expression of LvToll, transglutaminase, and prophenoloxidase genes when MI was offered daily as compared to the control group. The MI did not regulate the expression of the superoxide dismutase gene. The WSSV infection percentage decreased when feed with MI was offered every 3 d. Conclusion: The MI decrease WSSV infection percentage in L. vannamei infected with low viral load when it is offered every three days. The MI up-regulates LvToll, Tgase, and proPO genes when it is offered daily. Further research is needed regarding prophylactic treatment with microbial immunostimulants against WSSV in commercial shrimp farms.